Have you been drinking? - Chan, Grace Ying Xuan (2015)
As the games industry matures and evolves, there is an increasing need to develop innovative game experiences that meet the demands of gamers today. There are numerous factors to be taken into consideration when designing a game that builds up a significant degree of game experience. The concept of a game experience is commonly associated with the overall experience of playing a game including specific game elements such as graphics, sound and the player’s ability to control the game.